A Rare Case of Mosaic 3pter and 5pter Deletion-Duplication with Autism Spectrum Disorder and Dyskinesia - Luna Bajracharya; Meena Lall; Sunita Bijarnia-Mahay; Praveen Kumar; Imran Mushtaq; Pushpa Saviour; Preeti Paliwal; Anju Joshi; Shruti Agarwal; Praveen Suman (Case Reports in Genetics)
Introduction. There is evidence that neurodevelopmental disorders are associated with chromosomal abnormalities. Current genetic testing can clinch an exact diagnosis in 20–25% of such cases. Case Description. A 3 years and 11 months old boy with global developmental delay had repetitive behaviors and hyperkinetic movements. He was stunted and underweight. He had ataxia, limb dyskinesia, triangular face, microcephaly, upward slanting palpebral fissure, hypertelorism, retrognathia, posteriorly rotated ears, long philtrum, thin lips, broad nasal tip, polydactyly, tappering fingers, and decreased tone in the upper and lower limbs with normal deep tendon reflexes. Magnetic resonance imaging of the brain, ultrasound of the abdomen, and ophthalmological evaluation were normal. Brain evoked response auditory revealed bilateral moderate hearing loss. He fulfilled the Diagnostic Statistical Manual 5 criteria for autism. In the Vineland Social Maturity Scale, his score indicated a severe delay in social functioning. His genetic evaluation included karyotyping, fluorescence in situ hybridization (FISH), and chromosomal microarray analysis (CMA). The karyotype report from high-resolution lymphocyte cultures was mos 46, XY, der(3)t(3; 5)(p26; p15.3)[50]/46, XY,der(5) t(3;5) (p26;p15.3)[50].ish. His karyotype report showed a very rare and abnormal mosaic pattern with two cell lines (50% each). Cell-line#1: 3pter deletion with 5pter duplication (3pter−/5pter+) and cell-line#2: 3pter duplication with 5pter deletion (3pter+/5pter−) derived from a de novo reciprocal translocation t(3; 5)(p26; p15.3) which was confirmed by FISH. The chromosomal microarray analysis report was normal. The two cell lines (50% each) seem to have balanced out at the whole genome level. Occupational, sensory integration, and behavior modification therapy were initiated for his autistic features, and anticholinergic trihexiphenidyl was prescribed for hyperkinetic movements. Conclusion. This case highlights a rare genetic finding and the need for timely genetic testing in a child with dysmorphism and autism with movement disorder to enable appropriate management and genetic counselling.